CRIANÇAS FILOSOFANDO: uma proposta metodológica de ensino à luz de Matthew Lipman. - LIMA, Caroliny Santos (2018)
The present study deals with the theme: CHILDREN PHILOSOPHY: a methodological proposal of teaching in the light of Matthew Lipman, this research is born within the Postgraduate Program in Management of Basic Education – PPGEEB, Professional Master of the Federal University of Maranhão– UFMA, for this, we have a general objective: to construct a methodological proposal of teaching Philosophy for children in the light of Matthew Lipman in the perspective of forming a student who develops an education for thinking. And as specific objectives: To understand that theoretical and methodological conceptions of the teaching of Philosophy materialized in the form of themes transversal to the school that will be investigated possesses; To apprehend how the Basic Education Unit Henrique de La Roque Almeida can articulate child and Philosophy teaching; Elaborate a product that can meet the pedagogical and philosophical proposal of Matthew Lipman in the Basic Education Unit Henrique de La Roque. Following this delimitation, the research was characterized as being an intervention and for using the action-research methodology having as a delimitation the space of the UEB Henrique de La Roque Almeida, in the 3rd year of the 1st Cycle of Elementary Education. The subjects for the research were: teachers, parents and students. In this course, we develop the theoretical reference, making the relationship between Philosophy and childhood, its legal aspects and characteristics. We then proceed to the theoretical assumptions studied by Matthew Lipman, addressing the influences that Socrates, Charles Pierce, Vygotsky, and John Dewey had on their Philosophy for Children proposal. We also talked about the creator of the proposal, his life and what propelled him to create his program and methodology based on a research community. In order to direct the intervention, we draw the methodological steps for the analysis and interpretations of the subjects in light of the theoretical and methodological axes established along the same path, in this way of the pedagogical intervention we use the research instruments such as observations, interviews, focus groups, questionnaires and interventions in the classroom until reaching the product of the pedagogical intervention, the Notebook of Didactic Orientations. Having said this, we realize that Philosophy is the ideal space for the development of philosophical investigations.